1996
DOI: 10.1074/jbc.271.33.19732
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Natural Monomeric Response Elements of the Nuclear Receptor RZR/ROR. THEY ALSO BIND COUP-TF HOMODIMERS

Abstract: The receptor RZR/ROR is an important member of the nuclear receptor superfamily and has recently been shown to be the nuclear receptor for the pineal gland hormone melatonin. RZR/ROR binds as a monomer to DNA, and the human 5-lipoxygenase gene has been identified as the first RZR/ROR/melatonin-responding gene. Another prominent nuclear receptor is COUP-TF, which binds as a dimer to DNA. In this study, the sequences of known promoter regions of genes that may be involved in the physiological action of melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 48 publications
6
85
1
Order By: Relevance
“…This is compatible with the accepted concept that COUP-TF binds as a dimer, whereas ROR binds as a monomer. Indeed, COUP-TF homodimers have been shown to bind with high affinity to monomeric ROR/RZR response elements (Schräder et al 1996). In addition, COUP-TFII is also able to bind to a more downstream area ( 75 to 100) containing three (inverted) GGTCA repeats (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is compatible with the accepted concept that COUP-TF binds as a dimer, whereas ROR binds as a monomer. Indeed, COUP-TF homodimers have been shown to bind with high affinity to monomeric ROR/RZR response elements (Schräder et al 1996). In addition, COUP-TFII is also able to bind to a more downstream area ( 75 to 100) containing three (inverted) GGTCA repeats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…WAF/CIP1 and Purkinje cell protein-2 (Steinhilber et al 1995, Tini et al 1995, Schräder et al 1996, Vu-Dac et al 1997). …”
Section: Introductionmentioning
confidence: 99%
“…It remains to be determined whether ROR␣1 interacts with the TATA box-binding protein or rather competes for its binding, but its close localization to the TATA box and the requirement of an AT-rich nucleotide stretch for binding suggests that ROR␣ may compete for TATA box-binding protein binding resulting in a transcription initiation complex of higher activity. Although surprising, the identification of a potential similar TATA box overlapping RORE in the rat bone sialoprotein gene (36) suggests that ROR␣ may have a more general function as a component of the basal transcription machinery.…”
Section: Apoa-i Gene Regulation By Ror␣mentioning
confidence: 99%
“…However, the presence of the reported sequence requirements for ROR␣2 binding (a T at position Ϫ1 and an A at Ϫ4 relative to the AGGTCA half-site) in the apoA-I RORE (16,18) contrasts to the absence of ROR␣2 binding and transactivation on this RORE and suggests that other DNA sequence differences may also contribute to differentiate ROR␣1 from ROR␣2 binding. Computer homology searches allowed the identification of ROREs in a variety of genes, such as the human and mouse N-myc proto-oncogene, the mouse cellular retinol-binding protein I, chicken ␥F-crystallin, rat bone sialoprotein, mouse Purkinje cell protein 2, and human p21 WAF1/CIP1 (16,(35)(36)(37). In addition, a RORE has also been identified in the promoter of the 5-lipoxygenase gene, which may mediate the negative regulation of its expression by melatonin, a possible ligand for ROR/RZR␣ and ROR/RZR␤ (38 -40).…”
Section: Apoa-i Gene Regulation By Ror␣mentioning
confidence: 99%
“…RORA has also been suggested to be involved in lipid metabolism, to possess immunomodulatory activity and to mediate the antiarthritic properties of a class of thiazolidinediones (Missbach et al, 1996). ROREs (ROR response elements), to which RORA protein binds, have been identified in the promoter region of cell cycle-related genes, such as those of the cyclin-dependent kinase (CDK) inhibitor p21 WAF1/CIP1 (Schrader et al, 1996), and of cyclin A, as well as in the promoter of N-myc (Lee et al, 1984;Nau et al, 1986), a gene whose amplification appears to be related to the development of several tumors. It has been reported that ligand-induced activation of RORA significantly reduces the growth of the murine colon 38 adenocarcinoma (Pawlikowski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%